ANALISIS PERBANDINGAN KINERJA KEUANGAN PERBANKAN KONVENSIONAL DAN PERBANKAN SYARIAH TAHUN 2013 – 2017 - Marettha, Anggun; Puji Astuti, Dewi Saptantinah; Kristianto, Djoko (Universitas Slamet Riyadi, 2019)
The main problem in this study is whether there are differences in the financial performance of conventional banking and Islamic banking in terms of the ratio of LDR / FDR / NIM / NOM, CAR, ROA, NPL / NPF and BOPO in 2013 - 2017. The purpose of this study was to analyze the differences in the financial performance of conventional banking and Islamic banking in terms of the ratio of LDR / FDR, NIM / NOM, CAR, ROA, NPL / NPF, and BOPO in 2013 - 2017. The data used in this study were obtained from the Financial Statements of conventional banking and Islamic banking publications listed on the Stock Exchange from 2013 - 2017. After passing through the purposive sampling stage, the samples used were 8 conventional banks and 5 Islamic banks.The data analysis technique used to see the comparison of the financial performance of conventional banking and Islamic banking in 2013 - 2017 is to use financial ratio analysis and test the independent sample t-test. The analysis conducted shows that there are significant differences between conventional banking and Islamic banking in 2013 - 2017. Conventional banking financial performance is better than Islamic banking in terms of LDR / FDR, NIM / NOM, ROA, NPL / NPF and BOPO ratios, while Islamic banking financial performance is better than conventional banking in terms of CAR ratio.